Training the brain or tending a garden? Students’ metaphors of learning predict their self-reported learning patterns - Wegner, Elisabeth; Nückles, Matthias (Frontline Learning Research, 2016)
Conceptions of learning are seen as an important factor in shaping students’ patterns of learning. However, conceptions are often implicit and difficult to assess. Metaphors have been proposed as a method to assess conceptions, because metaphors are closely linked to the conceptual system. Therefore, in our study we assessed which conceptions of learning are visible in students’ metaphors of learning and examined whether these metaphors predict differences in students’ learning patterns. Altogether, N = 91 students of educational science from a German university filled in a questionnaire on their personal metaphors of learning, their learning strategy use, epistemological beliefs, and their motivation. Four kinds of metaphors could be differentiated: regulation-related metaphors, learning as knowledge acquisition, learning as problem solving, or as personality development. A discriminant analysis revealed that students with personality development metaphors and with problem solving metaphors were more intrinsically motivated and more aware of the relativism of knowledge than students with regulation-related or knowledge acquisition metaphors. Students with personality development metaphors differed from students with problem solving metaphors in their stronger use of deep processing strategies, their lower extrinsic motivation and their stronger rejection of a dualism of knowledge. The study demonstrates that metaphors of learning are a suitable tool for assessing students’ conceptions of learning and gives new insights on using this innovative method as an assessment tool.